2014
DOI: 10.1038/pj.2014.99
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled artificial viral capsid decorated with gold nanoparticles

Abstract: The decoration of a peptide-based artificial viral capsid with gold nanoparticles (AuNPs) is reported. β-Annulus GGGCG-bearing peptide as a binding site of AuNPs self-assembled into nanocapsules with a diameter of 50 nm. The addition of AuNPs to the peptide nanocapsules afforded relatively uncontrolled assemblies of AuNPs. In contrast, the self-assembly of AuNP-peptide conjugates afforded, after dialysis, controlled assemblies of AuNPs with sizes of 30-60 nm. ζ-Potential measurements revealed that the surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…Since the C‐terminus of the β‐annulus peptide is expected to be exposed on the outer surface when the capsid is formed, various binding motifs were introduced into the C‐terminus of the β‐annulus peptide for decoration of the outer surface with exogenous molecules. Decoration of gold nanoparticles (AuNPs) on the capsid was achieved by the construction of a AuNP‐β‐annulus peptide conjugate (Figure a) . A β‐annulus peptide possessing GGGCG at the C‐terminus was conjugated with AuNPs (5 nm) via thiol‐gold interaction at concentrations below CAC.…”
Section: Self‐assembled Artificial Viral Capsidsmentioning
confidence: 99%
“…Since the C‐terminus of the β‐annulus peptide is expected to be exposed on the outer surface when the capsid is formed, various binding motifs were introduced into the C‐terminus of the β‐annulus peptide for decoration of the outer surface with exogenous molecules. Decoration of gold nanoparticles (AuNPs) on the capsid was achieved by the construction of a AuNP‐β‐annulus peptide conjugate (Figure a) . A β‐annulus peptide possessing GGGCG at the C‐terminus was conjugated with AuNPs (5 nm) via thiol‐gold interaction at concentrations below CAC.…”
Section: Self‐assembled Artificial Viral Capsidsmentioning
confidence: 99%
“…Tomato bushy stunt virus (TBSV) capsids are formed by the self‐assembly of 180 quasi‐equivalent protein subunits containing 388 amino acids each and possess a dodecahedral internal skeleton composed of a C 3 ‐symmetric β ‐annulus motif . We demonstrated that the synthetic 24‐mer β ‐annulus peptide fragment (INHVGGTGGAIMAPVAVTRQLVGS) of TBSV spontaneously self‐assembled into virus‐like nanocapsules in water . The β ‐annulus motif was also found in other spherical viral capsids such as Sesbania mosaic virus (SeMV), desmodium yellow mottle tymovirus, ryegrass mottle virus, cucumber necrosis virus, tobacco necrosis virus, and turnip yellow mosaic virus .…”
Section: Introductionmentioning
confidence: 97%
“…4,29,30 We demonstrated that the synthetic 24-mer b-annulus peptide fragment (INHVGGTGGAIMAPVAVTRQLVGS) of TBSV spontaneously self-assembled into virus-like nanocapsules in water. [31][32][33][34] The b-annulus motif was also found in other spherical viral capsids such as Sesbania mosaic virus (SeMV), 35,36 desmodium yellow mottle tymovirus, 37 ryegrass mottle virus, 38 cucumber necrosis virus, 39 tobacco necrosis virus, 40 and turnip yellow mosaic virus. 41 SeMV capsids are formed through the self-assembly of 180 quasi-equivalent protein subunits composed of pentameric A and pseudohexameric B/C subunits.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, fluorescence ZnO nanoparticles were encapsulated in the artificial viral capsids self-assembled from ¢-annulus peptide bearing a ZnO-binding sequence (HCVAHR) at the N-terminal. 68 To decorate the artificial viral capsids with functional molecules, the C-terminal of ¢-annulus peptides were modified with 5 nm gold nanoparticles (AuNP) 69 and ODNs (dA 20 and dT 20 ). 70 AuNP¢-annulus peptide conjugate was prepared by mixing Cys-containing ¢-annulus peptide at the C-terminal with AuNPs at a concentration below the CAC followed by protection with thioctic acid.…”
Section: Artificial Viral Capsids Self-assembled From ¢-Annulus Peptidementioning
confidence: 99%
“…Molecular recognition of oligosaccharides by lectins (oligosaccharidebinding proteins) is known to increase as the oligosaccharides become denser, which is called the "multivalent effect" or the "glycocluster effect." 69 So far, artificial glycoclusters based on synthetic polymers showing such a multivalent glycocluster effect have been developed, not only as a model of molecular recognition involving glycolipids and glycoproteins but also as a cell culture substrate, material for trapping viruses and toxins, sensing material, drug delivery material, and regulating material of amyloid fibrils. 9 In densely arranged glycoclusters based on synthetic homopolymers such as polystyrene and polyacrylamide as the main chain, the lectin-recognizing ability may decrease due to steric hindrance in some cases.…”
Section: Introductionmentioning
confidence: 99%